Monitoring quality of care for patients with pancreatic cancer: a modified Delphi consensus. Issue 4 (April 2019) - Maharaj, Ashika D.; Ioannou, Liane; Croagh, Daniel; Zalcberg, John; Neale, Rachel E.; Goldstein, David; Merrett, Neil; Kench, James G.; White, Kate; Pilgrim, Charles H.C.; Chantrill, Lorraine; Cosman, Peter; et al.
Abstract: Background: Best practise care optimises survival and quality of life in patients with pancreatic cancer (PC), but there is evidence of variability in management and suboptimal care for some patients. Monitoring practise is necessary to underpin improvement initiatives. We aimed to develop a core set of quality indicators that measure quality of care across the disease trajectory. Methods: A modified, three-round Delphi survey was performed among experts with wide experience in PC care across three states in Australia. A total of 107 potential quality indicators were identified from the literature and divided into five areas: diagnosis and staging, surgery, other treatment, patient management and outcomes. A further six indicators were added by the panel, increasing potential quality indicators to 113. Rated on a scale of 1–9, indicators with high median importance and feasibility (score 7–9) and low disagreement (<1) were considered in the candidate set. Results: From 113 potential quality indicators, 34 indicators met the inclusion criteria and 27 (7 diagnosis and staging, 5 surgical, 4 other treatment, 5 patient management, 6 outcome) were included in the final set. Conclusions: The developed indicator set can be applied as a tool for internal quality improvement, comparative quality reporting, public reporting and research in PC care.